Integrated Metabolome and Transcriptome Analysis of Fruit Flavor and Carotenoids Biosynthesis Differences Between Mature-Green and Tree-Ripe of cv. “Golden Phoenix” Mangoes (Mangifera indica L.) - Peng, Lei; Gao, Wenke; Song, Miaoyu; Li, Minghai; He, Dinan; Wang, Ziran (Frontiers in Plant Science, 2022)
The commodity value of fruits is directly affected by fruit flavor and color. Secondary metabolites, such as amino acids, organic acids, esters, and β-carotene, are important synthetic products, which are of great significance in the flavor formation of mango fruits. In this study, a total of 309 different metabolites, consisting of organic acids, amino acids, phenolic acids, and saccharides, and a further 84 types of volatile organic compounds (VOCs) were identified in differential levels in TR vs. MG mango fruit stages. The major volatile compounds found were ester [2(3H)-furanone, 5-ethyldihydro; N-(2,5-ditrifluoromethylbenzoyl)-D-alanine, pentyl ester; and Octanoic acid, ethyl ester], aldehyde (benzaldehyde, 3-ethyl, and nonanal), and phenol [2-(1,1-dimethylethyl)-6-(1-methylethyl) phenol]. The analysis of carotenoid contents identified 68 carotenoids and we report for the first-time significant contents of zeaxanthin palmitate and (E/Z)-phytoene in mango fruits. α-carotene was a further major contributor to carotene contents with lesser contributions from 5,6epoxy-lutein-caprate-palmitate, β-carotene, lutein oleate, and β-cryptoxanthin. What is more, lutein content was significantly decreased in TR vs. MG fruit. RT-qPCR analysis revealed that relative to the MG stage, the expression of carotenogenic genes GGPS, PSY, LCYB, and ZEP was downregulated in TR mango fruit, whereas the transcript levels of PSD, CHYB, and NCED were downregulated. Additionally, the transcription level of some transcription factors (MYB, bHLH, and NAC) was highly correlated with pigment content in the pulp and may be responsible for carotenoid accumulation. The results describe major differences in metabolic pathways during the transition from MG to the TR stage of fruit ripening that are likely to contribute alterations in fruit flavor and provide several associated genes to be further studied in mango fruit.